Economic analysis for sizing of sugarcane (Saccharum spp.) mechanized harvesting - Santos,Neisvaldo B. dos (2014)
Sugarcane has a significant role on Brazilian agribusiness economy. The harvesting cane is considered as one of the most important operations of the process for it has to attend the raw material demanded by the sugar mill in quality and a competitive cost. The objective of this work it is it of analyzing, of systemic way, the variables influence on economical and operational performance in sugarcane mechanized harvesting process for sizing of machines. For this purpose a model called "ColheCana", was developed in a spreadsheet and in a programming language. The results showed that the field efficiency and harvester´s initial value are variables of great impact in the cost and that there is a maximum area that one equipment can attend and for this area the cost is minimum.